Removal of organic pollutants from produced water using Fenton oxidation - Afzal, T. (EDP Sciences, 2018)
Produced water (PW) is the largest stream of wastewater from oil and gas exploration. It is highly polluted and requires proper treatment before disposal. The main objective of this study was to investigate the effectiveness of Fenton oxidation in degradation of organic matter in PW. The role of operating factors viz., H2O2 concentration (0.12 Ã 10-3 moles/L to 3 moles/L), H2O2/Fe2+ molar ratio (2 to 75), and reaction time (30 to 200 minutes), on COD removal was determined through a series of batch experiments conducted in acidic environment at room temperature. The experiments were conducted with 500 mL PW samples in 1L glass beakers covered on the outside with aluminum foil to protect them from sunlight. Pre-decided amounts of ferrous sulfate heptahydrate (FeSO4.7H2O) and hydrogen peroxide (H2O2) were added to initiate the Fenton reaction. An increase in COD removal was observed with increase in reaction time and H2O2/Fe2+ molar ratio. COD removal also increased with H2O2 concentration up to 0.01 moles/L; further increase in H2O2 concentration decreased the COD removal efficiency. Over 90% COD removal was achieved under optimum reaction conditions. The study indicates that Fenton oxidation is effective for remediation of PW in terms of organic matter removal. Â© The Authors, published by EDP Sciences, 2018.